THE ROLE OF DYNAMIC CAPABILITY IN IMPROVING EXPORT COMPANIES’ COMPETITIVENESS AND PERFORMANCE - Muhammad Rusydi; Naidah Naidah; Syarifuddin Sulaiman (Program Pascasarjana STIE Amkop Makassar, 2019)
ABSTRACT Business competition at the international level is an important issue for companies, this is due to various different motives. This study aimed to identify and analyze the level of influence of dynamic capabilities on competitiveness and export performance. This research was conducted on export companies in South Sulawesi, Indonesia. The population in this study were the managers of each company, the sampling technique with sampling census so that the entire population was also a research sample. The main data collection was done by distributing questionnaires to the respondents. Secondary data in the form of export performance reports and other reports from BPS, the Department of Industry and Trade of the South Sulawesi Provincial Government, and PT Pelabuhan Indonesia IV (Persero). The analysis technique in this study deployed the Structural Equation Model. The results of the study shown that increasing dynamic capability had a positive and significant effect on increasing competitiveness in export companies, thus all dimensions in dynamic capability had a strategic contribution to the variable competitiveness. Competitiveness variables had a positive and significant effect on export performance in South Sulawesi. Increasing the competitiveness of export companies had an impact on increasing export performance. Dynamic capability variables had no significant effect on export performance. The originality in this study is the application of export performance models that establish dynamic capabilities as external factors, and then explain the role of dynamic capabilities on export performance through competitiveness. For practitioners, dynamic capability is an external factor which is very important in influencing competitiveness. Therefore export companies should be focus and maximize the role of dynamic capability as a macro factor that encourages increased export performance. Keywords: Dynamic Capability, competitiveness, performance, export, and strategy